Electroporation of germinated conidia and young mycelium as an efficient transformation system for Acremonium chrysogenum - Cruz-Ramón, Jessica; Fernández, Francisco J; Mejía, Armando; Fierro, Francisco (Folia microbiologica, 2019)
Three different transformation strategies were tested and compared in an attempt to facilitate and improve the genetic transformation of Acremonium chrysogenum, the exclusive producer of the pharmaceutically relevant β-lactam antibiotic cephalosporin C. We investigated the use of high-voltage electric pulse to transform germinated conidia and young mycelium and compared these procedures with traditional PEG-mediated protoplast transformation, using phleomycin resistance as selection marker in all cases. The effect of the field strength and capacitance on transformation frequency and cell viability was evaluated. The electroporation of germinated conidia and young mycelium was found to be appropriate for transforming A. chrysogenum with higher transformation efficiencies than those obtained with the conventional protoplast-based transformation procedures. The developed electroporation strategy is fast, simple to perform, and highly reproducible and avoids the use of chemicals toxic to cells. Electroporation of young mycelium represents an alternative method for transformation of fungal strains with reduced or no sporulation, as often occurs in laboratory-developed strains in the search for high-yielding mutants for industrial bioprocesses.
Keywords: elektroporace; Transformation, Genetic; transformace genetická; mycelium; mikrobiální viabilita; Spores, Fungal; Acremonium; Mycelium; Microbial Viability; Cephalosporins; Protoplasts; spory hub; fleomyciny; Drug Resistance, Bacterial; Electroporation; protoplasty; bakteriální léková rezistence; Phleomycins; cefalosporiny